BAD FAITH IN DAVID EBERSHOFF’S THE DANISH GIRL - Vanessa Marcelina; Yohanes Tuaderu (LINGUA LITERA : journal of english linguistics and literature, 2022)
Abstract Different people would have different perspectives on the meaning and purpose of life; some are scared to pursue it, while so me are keenen ough to explore. Any how, they all have to be responsible for the decision they choose. The Danish Girl, written by David Ebershoff, tells the story of a man and his journey to be coming a woman. As a man who has a feminine tendency, Einar Wegener lives his life as a man in bad faith to avoid unpleasant social interaction. As he gains the consciousness of his life’s meaning, he uses his freedom to decide to attempt to beauthentic. This research is conducted with a philosophical approach utilizing the existentialism theory of Jean-Paul Sartre. Sartre believed that human existence precedesessence, which means human beings are born without any principle. Consequently, they have to find their meaning and purposein life. The concept of bad faith isused to describe Einar’s life as a man. His transition to be coming a woman is analyzed with the concepts of authenticity and freedom. This research found that Einar Wegener’s life as a man is a form of bad faith. His authentic self is in the form of a woman named Lili. After containing his feminine side, Einar decided to transform fully into awomanintheact of fulfilling his meaning and purpose in life. Despiteh is failure at living authentically, he had the full consciousness to understand himself and had attempted to achieveit.